Effect of Exercise on Kidney Function, Oxidative Stress, and Inflammation in Type 2 Diabetic KK-Ay Mice. (26th July 2012) - Ishikawa, Yuji; Gohda, Tomohito; Tanimoto, Mitsuo; Omote, Keisuke; Furukawa, Masako; Yamaguchi, Saori; Murakoshi, Maki; Hagiwara, Shinji; Horikoshi, Satoshi; Funabiki, Kazuhiko; Tomino, Yasuhiko
Abstract : Exercise is recommended for the management of type 2 diabetes, but its effects on diabetic nephropathy (DN) are still unknown. We hypothesized that appropriate exercise improves early DN via attenuation of inflammation and oxidative damage. Type 2 diabetic KK-A y mice, a spontaneous DN model, underwent two different kinds of exercise (i.e., moderate and low intensity). Sedentary mice or those undergoing an exercise regimen causing no significant body weight loss were used. We examined the urinary excretion of albumin, number of podocytes and macrophages, renal expressions of HIF-1 α and MCP-1, and biomarkers of oxidative stress such as urinary 8-OHdG and serum SOD. Exercise reduced urinary levels of albumin and also maintained the number of podocytes in the exercised KK-A y mice independently of improvements of overweight and hyperglycemia, although moderate-intensity exercise increased expression of HIF-1 α . Sedentary KK-A y mice showed increased expression of MCP-1 and infiltration of macrophage, increased urinary 8-OhdG, and decreased serum SOD levels compared with exercised KK-A y mice. On the whole, low-intensity exercise attenuates progression of early DN without affecting marked renal ischemia. Reduction rates of urinary albumin and maintained podocyte numbers, with parallel improvements in oxidative damage and inflammation, are related to beneficial effects of exercise in diabetic kidney disease.